Social Science Research and School Diversity Policy. (March 2014) - Williams, Sheneka M.; McDermott, Kathryn A.
For decades, policy makers, advocates, and researchers have been engaged in efforts to make educational opportunity more equal for students from different racial, ethnic, and socioeconomic groups. A great deal of research has been conducted on their efforts; however, there is some disagreement on the extent to which the research has been influential. To examine the level of influence that social science research has had on school diversity policy, the authors conducted unstructured interviews with eight activists who use such research in arguments about school diversity. Findings from the study indicate that the influence of social science research is ambiguous, and to have influence, activists felt they had to target specific policy goals over a period of time.